Role of key point Mutations in Receptor Binding Domain of SARS-CoV-2 Spike Glycoprotein - Singh, Bipin (Infectious Disorders - Drug Targets, 2021)
The recent outbreak of novel coronavirus (SARS-CoV-2 or 2019-nCoV) and its worldwide spread is posing one of the major threats to human health and the world economy. It has been suggested that SARS-CoV-2 is similar to SARS-CoV based on the comparison of the genome sequence. Despite the genomic similarity between SARS-CoV-2 and SARS-CoV, the spike glycoprotein and receptor binding domain in SARS-CoV-2 shows the considerable difference compared to SARS-CoV, due to the presence of several point mutations. The analysis of receptor binding domain (RBD) from recently published 3D structures of spike glycoprotein of SARS-CoV-2 (Yan, R., et al. (2020); Wrapp, D., et al. (2020); Walls, A. C., et al. (2020)) highlights the contribution of a few key point mutations in RBD of spike glycoprotein and molecular basis of its efficient binding with human angiotensin-converting enzyme 2 (ACE2).
Keywords: 2019-nCoV